Efeito vasorelaxante do p-cimeno em artéria mesentérica isolada de rato - Barbosa, Renata Lisboa (2013)
The p- cymene is a monoterpene aromatic biosynthetic which has many biological properties , including cardiovascular. Em system actions on the in vivo study, p- cymene showed hypotensive activity through a central effect. Therefore, we sought to investigate the effect of p-cymene on the peripheral vascular resistance in the superior mesenteric artery of rats Rats were sacrificed by exsanguination under anesthesia and the superior mesenteric artery was removed, sectioned and kept in vats containing nutrient solution Tyrode. For recording of isometric contractions, each ring was suspended by cotton thread attached to a force transducer connected to a data acquisition system. In mesenteric artery rings with functional endothelium precontracted with phenylephrine (FE) (control), p- cymene (10-8 - 3x10 -2M) induced relaxation (Emáx = 77.1 ± 3.53% , n = 5) in a concentration-dependent manner not was attenuated after removal of endothelium (Emáx = 72 ± 4.03 %, n = 7) or pre-contracted with 80 mM KCl (Emáx = 79.37 ± 5.25 % n = 6) , suggesting a possible effect independent of the endothelium and surrounding channels for Ca2 +. In preparations without functional endothelium and pre-contracted with FEN and incubated with tetraethylammonium (TEA), tetraethylammonium (TEA), a blocker of non-selective for K+ channels, p- cymene induced relaxation (Emáx = 50.56 ± 4.09 %, n = 8) which was not significantly different from that obtained without functional endothelium in rings pre-contracted with FEN without blocking . Thus, possibly there is no involvement of K + channels for this purpose. Furthermore, incubation with p- cymene (3x10-3, 10-2 and 3x10-2M) was able to antagonize the contractions induced by CaCl2 (3x10-7 - 3x10-2M), and sodium orthovanadate (Na3VO4) (10-5 - 3x10-2M) a non-selective inhibitor of protein tyrosine fosfatase.These results it can be concluded that p- cymene produces vasorelaxant effect independent of the endothelium. The pharmacological evidence suggest that the mechanism of action of p- cymene vasorelaxant involves channels for Ca2+ and voltage sensitive desensitization of the Ca2+ contractile elements.